THE NON-LINEAR INTERACTION OF BRIDGES CONSTRUCTIONS AND THEIR INFRASTRUCTURE WITH FOUNDATION OF DISCRETE FLEXIBLE LANDING OF COMMON VIEW FOR EXAMPLE: CALCULATIONS, EXPERIMENTS AND DYING OUT VIBRATIONS - Kulyabko, V. V. (Science and Transport Progress, 2010)
In the article the issues of increasing the possibilities of computer modeling of the dynamic interaction of bridge constructions and their infrastructure with moving transport and flows are considered.